2013
DOI: 10.5812/jjm.4866
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cutaneous Leishmaniasis Agents in Four Geographical Regions of Khuzestan Province Using Nested PCR

Abstract: Background: Leishmania tropica and Leishmania major are the main causes of cutaneous leishmaniasis in endemic regions of Iran. Objectives: The aim of this study was the identification of cutaneous leishmaniasis agents in Khuzestan province located southwest of Iran. Patients and Methods: 146 samples were collected from the lesions of 146 individuals including 67 (59.59% ) male and 59 ( 40.41% ) female with cutaneous leishmaniasis. The samples were then delivered to Iran-Zamin diagnostic laboratory and smeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Khuzestan province is endemic for ZCL and had an overall prevalence rate of 37.39/100,000. Recently, L. tropica has been detected in a minority of patients with prevalence rates ranging from 3 to 10%, including in the ancient city of Shush (10% rate) in northern Khuzestan (50,51). Data in 2013 from the mountainous province of Lorestan showed a predominance of L. tropica; overall, 72% (45/64) of local CL patients were infected by L. tropica, notably from Poldokhtar (37/43, 86%) and Kouhdasht (4/5, 80%).…”
Section: Western Iranmentioning
confidence: 99%
“…Khuzestan province is endemic for ZCL and had an overall prevalence rate of 37.39/100,000. Recently, L. tropica has been detected in a minority of patients with prevalence rates ranging from 3 to 10%, including in the ancient city of Shush (10% rate) in northern Khuzestan (50,51). Data in 2013 from the mountainous province of Lorestan showed a predominance of L. tropica; overall, 72% (45/64) of local CL patients were infected by L. tropica, notably from Poldokhtar (37/43, 86%) and Kouhdasht (4/5, 80%).…”
Section: Western Iranmentioning
confidence: 99%
“…Another molecular study used real-time PCR and melt-curve analysis by Kinetoplast DNA primers on 102 archived slides, emphasizing L. major as the predominant strain (93.75%), based on our results in the southwest of Iran (30). A nested-PCR approach was also performed on 146 clinical samples in four geographical regions of the province by Maraghi et al, again with L. major as the prevailed species (94.5%), followed by L. tropica (5.5%) (31). In addition, a mini-exon PCR-RFLP study was conducted on 14 clinical cutaneous lesions of suspected patients from a different region of the province; the results identified 12 cases as L. major and only two cases as L. tropica.…”
Section: Discussionmentioning
confidence: 78%
“…In the current study, the amplification of ITS1 gene fragment with 350 bp showed clear band when electrophoresis on 2% agarose gel. Belal et al, (2012) (Maraghi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%